2020
DOI: 10.3390/s20226691
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validation of an E-Textile-Based Wearable Sock for Remote Gait and Postural Assessment

Abstract: This paper presents a new wearable e-textile based system, named SWEET Sock, for biomedical signals remote monitoring. The system includes a textile sensing sock, an electronic unit for data transmission, a custom-made Android application for real-time signal visualization, and a software desktop for advanced digital signal processing. The device allows the acquisition of angular velocities of the lower limbs and plantar pressure signals, which are postprocessed to have a complete and schematic overview of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…Cognitive functions, mainly executive functions, are related to gait pattern, coordination, and balance. They can explain motor syndrome associated with mild cognitive impairment and dementia as described by other authors [ 40 , 44 , 45 ]. Recently Mulas et al [ 46 ] published the results of gait assessment in Italian cognitive impaired older adults using wearable inertial sensors finding a significant reduction of speed in these patients and other changes in gait parameters.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Cognitive functions, mainly executive functions, are related to gait pattern, coordination, and balance. They can explain motor syndrome associated with mild cognitive impairment and dementia as described by other authors [ 40 , 44 , 45 ]. Recently Mulas et al [ 46 ] published the results of gait assessment in Italian cognitive impaired older adults using wearable inertial sensors finding a significant reduction of speed in these patients and other changes in gait parameters.…”
Section: Discussionmentioning
confidence: 65%
“…Likewise, Vallabhajosula et al [ 24 ] conducted a study to validate their technological device based on pressure sensors to measure gait patterns and found that concurrent validity was acceptable. Also, a recent study conducted by Amitrano et al [ 40 ] validates a new wearable e-textile based system (SWEET Sock) for remote gait and postural assessment. It is of utmost importance to incorporate these devices in consultation to speed up the assessment process and to be able to anticipate risks of falls or deterioration of muscle health.…”
Section: Discussionmentioning
confidence: 99%
“…They performed a benchmarking analysis between the proposed device and the related gold standard, showing good agreement with an error lower than 1%. Amitrano et al [ 61 ] proposed a new wearable e-textile based system for biomedical signals remote monitoring able to acquire angular velocities of the lower limbs. Specifically, the system equips an IMU and textile pressure sensors made of EeonTex, namely a conductive and nonwoven microfiber with piezo-resistive functionality, which were placed correspondingly between the ankle and the plantar zone of the considered (3) HCs, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are supportive of new algorithms and applications that allow continuous measurement of gait velocity and cadence via the smartphone, placed on the body, in a bag, or on a belt [ 42 , 43 ]. Additional technologies that acquire spatio-temporal gait parameters include E-Textile-Based wearable socks [ 44 ], Inertial Measurement Units (IMU) [ 45 ], Hall-effect sensors [ 46 ], and smartwatches [ 47 ]. A thorough list of wearable sensors used for gait analysis is detailed in [ 46 ].…”
Section: Discussionmentioning
confidence: 99%